Design and performance optimization of vehicle-mounted thermal snow-melting system - Zhaoran Li; Yanqing Sheng; Weihan Xu (PLoS ONE, 2025)
Snow clearing and melting vehicles do not need to transport snow out of the country, which helps to alleviate traffic congestion and has broad market prospects. In this study, a vehicle-mounted thermal snow-melting system was designed and the performance of the thermal snow-melting system was simulated. Then, the influences of the entry and exit modes, flow rate of the heat medium, and scraper speed on the snow melting rate were analysed. Studies have shown that thermal snowmelt systems are well designed and have good stability and availability. The speed of the scraper significantly affects the rate of snow melting. As the speed of the scraper increases from 0 r/min to 42 r/min, the time required for complete snow melting was reduced to approximately 1/25 of the original. The flow rate of the thermal medium has a small effect on the rate of snow melting. The time taken for the snow to melt completely under the internal inlet and external outlet method is 1.2 to 2.3 times longer than that of the external inlet and internal outlet method. The rank of influence degree was scraper speed>  entry and exit modes>  flow rate when the target was the maximum melting rate. This research provides a scientific basis for the manufacture of integrated snow clearing and melting equipment.